INOVASI TANPA BATAS POTENSI AI DALAM MENCIPTAKAN SISTEM TRANSAKSI KEUANGAN DIGITAL - Devita Nurwulan; Fiqri Cahya Maulana; Tri Handoyo Prisasti (CV. KAMPUS AKADEMIK PUBLISING, 2025)
In this era of digitalization, artificial intelligence (AI) has emerged as one of the most revolutionary innovations, paving the way for efficiency, speed, and security in various financial transactions. This study employs a literature review method with a qualitative approach. According to Sugiyono (2019), descriptive qualitative research aims to gain a deep understanding of phenomena through the analysis of secondary data such as books, journals, and related documents. The advancement of AI in creating financial reports minimizes human error and increases the speed of completion. Additionally, this technology is capable of performing predictive analysis, providing companies with deeper insights into their financial conditions. The implementation of artificial intelligence (AI) in digital financial transaction systems has opened a new chapter in the financial world, making it more efficient, secure, and inclusive. AI enables process automation, enhanced data security, and personalized services that address the needs of modern society